The Presence of Organochlorine and Organophosphate Pesticide Residue in Groundwater at the Upper Citarum Watershed - Deviyani, Deviyani; Oginawati, Katharina; Salami, Indah Rahmatiah Siti (Journal of Engineering and Technological Sciences, 2026)
Chemical residue, particularly pesticide from agricultural activities at the Citarum Upper Watershed, is considered an evolving contaminant due to the presence in groundwater samples. Therefore, this qualitative study aims to identify four pesticide residues from organophosphate (OPP) and organochlorine (OCP). Groundwater grab sampling method was applied to collect 31 samples from each location. Extraction was then carried out using the QuEChER preparation technique, followed by gas chromatography-mass spectrometry (GC-MS) analysis. The results showed that Dichlorodiphenyltrichloroethane (DDT) had the highest concentration at 0.1062 mg/L. Chlorpyrifos had the highest detection above the limit of detection (LOD) in 13 groundwater samples, with concentrations ranging from 0.0116 to 0.2469 mg/L. Lindane and diazinon were also detected, with maximum concentrations of 0.03209 mg/L and 0.0698 mg/L, respectively. Risk assessment was further carried out to determine the chronic and acute Hazard Quotient (HQ) for all residue. Dichlorodiphenyltrichloroethane and lindane scored > 1 at maximum concentration in adults, while diazinon was at an acceptable level for all scenarios. However, when children-specific parameters were applied, chlorpyrifos demonstrated HQ>1, suggesting additional health risk for children in the area. Immediate studies of pesticide exposure on public health, specifically in children from the site, are essential due to the critical stages in life.